Clinical validation of a novel smartphone application for measuring best corrected visual acuity - Ogino, Mari; Salmerón-Campillo, Rosa María; Hunter, Stephen; Hussey, Vincent; Suh, Donny; Gore, Rujuta; López-Gil, Norberto; Jaskulski, Matt; Piña-Miguelsanz, Daniel (Journal of optometry, 2023)
Personal mobile devices such as smartphones are proving their usefulness in ever more applications in tele-eyecare. An inconvenience and potential source of error in these past approaches stemmed from the requirement for the subjects to situate their devices at a distance. The present study aims to clinically validate best corrected visual acuity (BCVA) measures carried out by a novel smartphone application “vision.app” (VisionApp Solutions S.L.) using comparative statistics against clinical measurements. BCVA was measured in both eyes of 40 subjects using vision.app which displayed a black Landolt-C optotype with crowding on a white background, and utilized a 4 forced-choice procedure for the subjects to find (by means of swiping in either of four directions) the smallest optotype size they could resolve. Results were compared to BCVA measurements taken using a standard Snellen chart placed at 20 feet (6 m). The t-test revealed no significant differences between the app- and clinically-measured VA (p = 0.478 (OD) and 0.608 (OS)), with a mean difference between clinical and app measurements of less than one line of the eye chart (-0.009 logMAR (OD) and -0.005 logMAR (OS)). A limit of agreement for a 95% confidence interval of ± 0.08 logMAR for OD and OS was found. The results show the potential use of a smartphone to measure BCVA at a handheld distance. The newly validated study results can hold major future advancements in tele-eyecare and provide eye care professionals with a reliable and accessible method to measure BCVA.